Review of local wound management for scleroderma-associated digital ulcers. Issue 1 (February 2018) - Lebedoff, Nicholas; Frech, Tracy M.; Shanmugam, Victoria K.; Fischer, Aryeh; Erhardt, Daniel; Kolfenbach, Jason; Kohler, Kevin; Bernhisel, Kurt; Lewis, Giavonni M.
Digital ulcers (DU) are a common clinical problem in systemic sclerosis (SSc); however, there is no standardization of local wound care protocols for management of these lesions. There is a well-recognized need to develop and standardize non-pharmacological management of DU in patients with SSc, and to adopt these protocols in future clinical trials that focus on DU healing. The purpose of this review is to outline the types of DU that occur in SSc, and provide an update on the principles of wound management for these lesions based on the current literature and expert opinion.